Co – creation Approaches to Improve Conservation Efforts of African Elephant Populations in Nigeria - J Fada, Salamatu; C. Omotoriogun, Taiwo; O. Amusa, Tajudeen; A. Danmallam, Bello; Solomon Kumdet, Panshak; Akintunde, Elijah; Zakari Muhammad, Naziru (European Journal of Sustainable Development, 2024)
Scientific sources and the IUCN reveal the decline in African Elephant populations, and new Redlist status for both the Forest and Savannah African Elephants. Efforts are ongoing to improve conservation of Forest and Savannah Elephants in Nigeria through engagement of local communities adjoining Protected Areas. This study investigates the willingness of local communities to co-create approaches that support elephants